2005
DOI: 10.1074/jbc.m500747200
|View full text |Cite
|
Sign up to set email alerts
|

Protease-activated Receptor-1 Signaling by Activated Protein C in Cytokine-perturbed Endothelial Cells Is Distinct from Thrombin Signaling

Abstract: Activated protein C (APC) has anti-inflammatory and vascular protective effects independent of anticoagulation. We previously identified the prototypical thrombin receptor, protease-activated receptor-1 (PAR1), as part of a novel APC-endothelial cell protein C receptor (EPCR) signaling pathway in endothelial cells. Experiments in wild-type and PAR1؊/؊ mice demonstrated that intravenous injection of APC leads to PAR1-dependent gene induction in the lung. The vascular endothelium undergoes profound changes in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
177
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(189 citation statements)
references
References 44 publications
9
177
0
3
Order By: Relevance
“…The role of EPCR as a crucial co-receptor for PC activation and aPC-mediated cytoprotective signaling in vascular and immune cells is supported by in vitro and in vivo data (57)(58)(59)(60)(61)(62)(63). However, TF is normally not expressed in the vascular endothelium but co-expressed with EPCR in extravascular cells.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The role of EPCR as a crucial co-receptor for PC activation and aPC-mediated cytoprotective signaling in vascular and immune cells is supported by in vitro and in vivo data (57)(58)(59)(60)(61)(62)(63). However, TF is normally not expressed in the vascular endothelium but co-expressed with EPCR in extravascular cells.…”
Section: Discussionmentioning
confidence: 76%
“…The presented data with SMCs raise the intriguing possibility that TF and EPCR expressed in the vessel wall regulate the cellular responses to low levels of coagulation proteases that are constitutively present or ectopically synthesized in the extravascular space. Intravascular EPCR-aPC-PAR1 signaling counteracts thrombin-PAR1 signaling (8,57,61,76). It is intriguing to speculate that EPCR-dependent ternary complex signaling may similarly regulate certain aspects of extravascular upstream coagulation signaling.…”
Section: Discussionmentioning
confidence: 99%
“…2,[25][26][27][28] Plasmin either activates or disarms PAR1, 6,29,30 whereas it inactivates PAR2 and activates PAR4. 31,32 The activated protein C (APC) has been shown to activate PAR1 and PAR2, [33][34][35] although its functional role still remains controversial. 36 In the following sections, I would like to discuss the role of PARs in regulating the vascular functions and in the pathophysiology of vascular diseases, with some focus on thrombin and its major receptor PAR1.…”
mentioning
confidence: 99%
“…A previous study showed that under hypoxic conditions, p38 mitogen-activated protein kinase (p38MPAK) is essential for fibroblast proliferation and acts as a modulator of pro-inflammatory responses in rheumatological conditions (Mortimer et al 2007). Indeed, if protease-activated receptors (PARs) are activated, they signal via p38 to induce immune responses (Julovi et al 2011;Riewald & Ruf 2005). Thus, we expected that activation of p38 by APC under hypoxic conditions would be involved in the proliferation and anti-inflammatory response of RAFb.…”
Section: Discussionmentioning
confidence: 99%